Assessment of the alien marine intertidal invertebrates in the Kogelberg Biosphere Reserve, South Africa - Malherbe, Hanlie (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScConEcol)--UnStellenbosch University, 2011.